Intersecting substance use treatment and harm reduction services: exploring the characteristics and service needs of a community-based sample of people who use drugs - Noa Krawczyk; Sean T. Allen; Kristin E. Schneider; Keisha Solomon; Hridika Shah; Miles Morris; Samantha J. Harris; Susan G. Sherman; Brendan Saloner (BMC, 2022)
Abstract Background Substance use treatment and harm reduction services are essential components of comprehensive strategies for reducing the harms of drug use and overdose. However, these services have been historically siloed, and there is a need to better understand how programs that serve people who use drugs (PWUD) are integrating these services. In this study, we compared treatment and harm reduction services offered by a multistate sample of substance use service providers and assessed how well they align with characteristics and needs of clients they serve early in the COVID-19 pandemic. Methods We recruited a convenience sample of programs that deliver harm reduction and/or treatment services in ten US states. Program directors participated in a survey assessing the services offered at their program. We also recruited clients of these programs to participate in a survey assessing a range of sociodemographic and health characteristics, substance use behaviors, and health service utilization. We then cross-compared client characteristics and behaviors relative to services being offered through these programs. Results We collected and analyzed data from 511 clients attending 18 programs that we classified as either offering treatment with medications for opioid use disorder (MOUD) (N = 6), syringe service programs (SSP) (N = 8), or offering both MOUD and SSP (N = 4). All programs delivered a range of treatment and harm reduction services, with MOUD & SSP programs delivering the greatest breadth of services. There were discrepancies between services provided and characteristics and behaviors reported by clients: 80% of clients of programs that offered MOUD without SSP actively used drugs and 50% injected drugs; 40% of clients of programs that offered SSP without MOUD sought drug treatment services. Approximately half of clients were unemployed and unstably housed, but few programs offered direct social services. Conclusions In many ways, existing programs are not meeting the service needs of PWUD. Investing in innovative models that empower clients and integrate a range of accessible and flexible treatment, harm reduction and social services can pave the way for a more effective and equitable service system that considers the long-term health of PWUD.